Characterization of beef cattle farming in the Atlantic Zone of Costa Rica - Loon, M. van (CATIE, Turrialba (Costa Rica) Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
46 pág, 1 ilus, 11 tab, 22 ref. También como: Field Report Atlantic Zone Programme (CATIE) no. 168